RESVERATROL INHIBITS CANONICAL WNT SIGNALING AND AMELIORATES EXPERIMENTAL ARTHRITIS - Koca, S. S.; Yolbas, S.; Yildirim, A.; Celik, Z. B.; Onalan, E. E.; Akin, M. (Bmj Publishing Group, 2016)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 08-11, 2016 -- London, ENGLAND